2013
DOI: 10.1016/j.rehab.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a motor function classification in patients with neuromuscular disease: The NM-Score

Abstract: The NM-Score is a reliable, reproducible outcome measure with value in clinical practice and in clinical research for the description of patients and the constitution of uniform patient groups (in terms of motor function).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…13 Its reproducibility was considered good. For D1, D2, and D3, the levels of agreement between raters were 82.9%, 78.1%, and 75.6%, and the kappa coefficients were .77, .69, and .64, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Its reproducibility was considered good. For D1, D2, and D3, the levels of agreement between raters were 82.9%, 78.1%, and 75.6%, and the kappa coefficients were .77, .69, and .64, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…13 Based on a statement by the World Health Organization about the potential influence of personal and environmental factors on the way patients with NMDs manifest their mobility capacities, 9 the NM-Score focuses on motor function performance under typical current circumstances, not under controlled test conditions.…”
mentioning
confidence: 99%
“…Actually, although our sample size was smaller (n = 51) and the patients were younger (7-21 years) than those of Berard et al 's study (10), the variety of the NMDs was similar as they consisted of DMD (n = 25), myopathy (n = 9), SMA (n = 5), BMD (n = 5), polyneuropathy (n = 5), and Friedreich ataxia (n = 5) patients. They found that "agreement coefficients for interrater reliability were excellent for nine items, good for 20 (19) have also reported in a study in 448 patients with genetic neuromuscular diseases that the MFM-32 was a reliable, reproducible, and valuable outcome measure for clinical practice and research, since it was able to describe the physical status of patients and formulate the uniform patient groups according to motor function.…”
Section: Discussionmentioning
confidence: 85%
“…The validated Motor Function Measure scale, items 13 to 23, was used to evaluate the sitting position, function of the arms, neck and head control in the patient group. 26,27 Masticatory Training At the start of the masticatory training all participants received a box including 3 chewing gum packs, stopwatch and a diary. All participants followed the same program which was written on the back side of the box and on the chewing gum wrappers.…”
Section: Physical Abilitiesmentioning
confidence: 99%
“…In the healthy subjects, a significant difference could be demonstrated between measurements at T 1 or T 2 regarding the protrusion, albeit within the smallest detectable change of 2 mm (Table 2). 27 …”
Section: Clinical Examination Of the Masticatory Systemmentioning
confidence: 99%